DIGITAL LEADERSHIP COMPETENCIES AND ORGANIZATIONAL ADAPTABILITY IN UNCERTAIN ECONOMIES - Mochammad Isa Anshori; Maulinda Hasanah (Adisam Publisher, 2026)
This study aims to analyze the relationship between digital leadership competencies and organizational adaptability in uncertain economic conditions through a literature review approach. The study employs a qualitative literature review by systematically examining recent scientific publications from reputable national and international journals, books, and scholarly reports relevant to digital leadership, organizational adaptability, and economic uncertainty. The collected literature was analyzed using thematic analysis to identify recurring concepts, patterns, and theoretical relationships. The findings indicate that digital leadership competencies, including digital literacy, strategic vision, innovation capability, data-driven decision-making, agile leadership, collaborative communication, and change management, play a pivotal role in strengthening organizational adaptability. These competencies enable organizations to respond proactively to environmental volatility, technological disruption, shifting market demands, and emerging organizational risks. The study concludes that digital leadership competencies represent a strategic capability for sustaining organizational performance and competitiveness in uncertain economies. The findings contribute to the development of digital leadership literature and provide practical insights for organizations seeking to enhance adaptive capacity amid rapidly changing business environments.